Moralising class: A discourse analysis of the mainstream political response to Occupy and the August 2011 British riots. (January 2013) - Bennett, Joe
In this article, I present an analysis of the discursive response of two British politicians – the Prime Minister David Cameron and the leader of the opposition, Ed Miliband – to the riots that took place in British cities in August 2011 and the Occupy protests of later in the same year. Considering this response as, following Van Leeuwen, recontextualisation of the events with which the two politicians are concerned, I suggest that in both cases a particular neoliberal discourse is employed that serves to moralise what is in actual fact material, class-based opposition. Cameron suggests that the riots are indicative of a 'moral collapse' in contemporary Britain, and Miliband, superficially aligning himself with the movement, suggests that the Occupy protests indicate a 'value gap'. In both cases, I argue, the discursive response serves as an attempt to assert as hegemonic a substantively identical moralised neoliberal understanding of the inequalities of contemporary capitalism. This is an understanding – a discourse – that I suggest is both a contributor to these inequalities and a false representation of their true nature.